Transformarea analizei financiare în contextul practicilor contabile moderne - Bogos (Calancea), Eugenia (CEP USM, 2024)
The transformation of financial analysis within modern accounting practices is a critical development in the financial landscape. This article explores the impact of digitalization and technological advancements on accounting, emphasizing the importance of modern accounting practices and the consequent evolution of financial analysis. By examining the integration of technologies such as artificial intelligence, cloud computing, and blockchain, we highlight how these innovations enhance efficiency, accuracy, and strategic decision-making. The findings illustrate that the shift towards automated, real-time financial analysis is not merely a trend but a necessity for organizations aiming to thrive in a competitive environment.
The transformation of financial analysis in the context of modern accounting practices
Keywords: accounting; financial analysis; financial management; strategy